An integrated management for the control of bacterial wilt of tomato caused. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2004)
An evaluation on the effect of two tomato varieties, MT 11 and Pearl, treated with combination of two strains of Pseudomonas putida, Ca (NO3)2 and With/without Stonier's medium, on the incidence of bacterial Wilt, was carried out in the field. Tomato seeds were bio-primed with combined strains of antagonist, KTS 26 and AC1. Four-week old seedlings were transplanted to the field, which were artificially infested with the pathogen, to ensure even and high inoculum density. Application of Ca (NO3)2 were done at regular intervals before and after transplanting. Stonier's medium was applied 4 days before transplanting. For each variety, non-treated plants served as control. Results showed that the antagonist and Ca (NO3)2 treatments were not able to provide any resistance to the susceptible Pearl tomato variety which, recorded 100% infection.